PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS MODEL PROBLEM BASED LEARNING PADA MATERI BENTANG ALAM DARATAN DAN PERAIRAN KELAS III SD NEGERI 1 SRIKATON KABUPATEN TULUNGAGUNG - Cahyawati, Inne Dwi; Rohmatus Syafi’ah; Sari, Eka Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an animated video learning media based on the Problem Based Learning (PBL) model on the topic of Land and Water Landforms for third-grade students at SD Negeri 1 Srikaton, Tulungagung Regency. This research used the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The animated video was developed using the Canva application with a duration of 6 minutes in HD MP4 format. Data collection instruments used were validation questionnaires assessed by three media experts, three material experts, and three language experts, as well as response questionnaires filled out by 24 third-grade students and one classroom teacher. The results showed that the media achieved a very valid category based on media expert assessment with an average score of 4.63, material expert assessment with an average score of 4.85, and language expert assessment with an average score of 4.63. The practicality test results obtained a student response percentage of 91.94% and a teacher response percentage of 95%, both categorized as very practical. It can be concluded that the animated video learning media based on the PBL model is valid and practical for use in science and social studies (IPAS) learning in elementary schools.